Autogenous Healing in Strain-Hardening Cementitious Materials With and Without Superabsorbent Polymers: An 8-Year Study - Snoeck, Didier; De Belie, Nele (Frontiers in Materials, 2019)
To obtain a more sustainable concrete, its occurring cracks should be repaired. However, as manual repair is time-consuming and expensive, self-healing may provide a proper solution. Autogenous healing is an already present feature in cementitious materials, but it is an inferior mechanism as it can only completely heal cracks up to 30 µm in the presence of water. Therefore, a cementitious material with synthetic microfibers to limit the crack widths and superabsorbent polymers (SAPs) to provide the necessary water was proposed. However, due to ongoing hydration, autogenous healing based on further hydration of unhydrated cement may be less efficient in time. In this study, the ability of autogenous healing in time (on specimens with an age of 7 days, 28 days, 3 months, 1 year, 3 years and 8 years) is investigated by comparing the mechanical characteristics after performing four-point-bending tests. The specimens were first loaded to 1% strain at their respective age, stored in a specific healing condition (a relative humidity of 60%, more than 90% and wet/dry cycles) for 28 days and were subsequently reloaded. The results show that, with increasing age, the mean crack width decreases. All specimens are able to partially heal and to regain some of the mechanical properties after being preloaded and re-cracked under four-point-bending. If SAPs are added, there is partial healing in an environment without liquid water (more than 90% RH). At early age, the healing is governed by further hydration and calcium carbonate crystallization. From three months onwards, the main autogenous healing mechanism is calcium carbonate crystallization. Overall, mixtures with SAPs generally showed more self-healing and are thus a promising material to be used in future building applications.